Toxic Epidermal Necrolysis In Human Immunodeficiency Virus Infection - Rao Venkareswara M; Mohan Thappa Devinder (Wolters Kluwer Medknow Publications, 1997)
Toxic epidermal necrolysis following ATT in HIV patient is reported. The role of HIV in drug reactions is discussed .